Numerical study on static performance of hydrodynamic bearing in high-speed liquid hydrogen centrifugal pump. (12th January 2023) - Lai, Tianwei; Yan, Shaohang; Wang, Yanwu; Liu, Xue; Qiang, Mingchen; Ding, Wenjing; Liu, Yutao; Hou, Yu
Abstract: High speed liquid hydrogen centrifugal pump is regarded as one of the most potential transmitting equipment in hydrogen distribution. Due to the cryogenic physical properties of liquid hydrogen, lubrication in the high-speed pump remains a challenge for its further application. In this paper, a novel grooved bearing using liquid hydrogen as lubricant has been proposed for long term reliable operation. Static performances of the bearing, including pressure distribution, vapor volume fraction and load capacity, have been evaluated numerically focusing on the cavitation effect. Considering the coupled effects in the bearing, orthogonal design method is used to optimize the structural parameters. With the optimal parameters, the load capacities of both journal and thrust bearing can be improved by 30% and 50%, respectively. In addition, the optimized coupled bearing can suppress the cavitation effectively, which is expected to be used in high-speed centrifugal pump with long-term and stable operation. Graphical abstract: Image 1 Highlights: Feasibility of LH2 lubrication has been presented for high speed cryogenic pump. A L-type coupled bearing lubricated by LH2 is proposed for better performance. The coupled effect is revealed considering cavitation with thermodynamic effects. Structure parameters of coupled bearings are optimized using orthogonal method. Performance variation of optimized L-type bearing with speed is investigated.